The role of the family in achieving intellectual security among children: Social study - AlKetbi, Rawda; Al-Othman, Hussain (Al-Adab Journal, 2025)
This study aims to identify the extent of the impact and contribution of the family in enhancing the intellectual security of social, cultural, religious and psychological children, relying on an analytical study that focused on describing and analysing the reality of the role of the family and its contribution to the formation of intellectual immunity among children, and this study has shown what intellectual security, which is part of the public security system in society The study also dealt with the types of intellectual security and the challenges it faces by relying on studies that dealt with the subject of intellectual security in its various aspects, and the results concluded that enhancing intellectual security among children passes through several stages, starting from the stage of prevention and formed through the role of the family in instilling societal, religious and cultural values from a young age, and then the stage of confrontation with discussion and dialogue that includes arguments and proofs to refute deviant ideas, and finally the stage of treatment and evaluation to correct and evaluate thought and correct it, These stages contribute to the formation of the individual's personality as a personality capable of analysis, criticism and self-reliance, in front of social change and cultural momentum.